2017
DOI: 10.3892/or.2017.5716
|View full text |Cite
|
Sign up to set email alerts
|

The function of miRNAs in hepatocarcinogenesis induced by hepatitis B virus X protein

Abstract: MicroRNAs are short RNAs that play a crucial role in all biological processes through post-transcriptional regulation for protein-coding genes and inducing mRNA degradation. Hepatitis B virus infection has been considered as a major risk factor in hepatocellular carcinoma, further research indicates that hepatitis B virus X protein (HBx) is one of the critical links of hepatocarcinogenesis. HBx takes part in hepatocarcinogenesis via regulating transcription, signal transduction, apoptosis, protein degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 130 publications
0
9
0
Order By: Relevance
“…For example, miR-34a,9 miR-506,10 and miR-64511 are downregulated in HCC, whereas miR-197,12 miR-552,13 and miR-65014 are expressed at high levels in HCC. The dysregulated miRNAs exert their functions as oncogenes or tumor suppressors and play crucial roles in the initiation and progression of HCC 1517. Therefore, therapies that target miRNAs may be attractive strategies for HCC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-34a,9 miR-506,10 and miR-64511 are downregulated in HCC, whereas miR-197,12 miR-552,13 and miR-65014 are expressed at high levels in HCC. The dysregulated miRNAs exert their functions as oncogenes or tumor suppressors and play crucial roles in the initiation and progression of HCC 1517. Therefore, therapies that target miRNAs may be attractive strategies for HCC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] An increasing number of studies have proven that miRNAs are the main drivers of HCC tumorigenesis because they function as oncogenes or tumor suppressor genes. [37][38][39] Moreover, miRNA-based targeted therapies have been tested in several preclinical models, including HCC models. 40 Therefore, identification of oncogenic or tumor-suppressive miRNAs and detailed elucidation of their roles in HCC pathogenesis may help identify effective biomarkers for HCC diagnosis and prognosis as well as therapeutic targets in this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that miRNAs are involved in the proliferation, differentiation, migration, and apoptosis of liver cancer cells. 2 It is well known that miR-183 is upregulated in HCC and is considered to be an oncomiR. Functionally, the miR-183 family (miR-183, -96 and -182) promotes the cellular invasion and migration of HCC cells.…”
Section: Introductionmentioning
confidence: 99%